ChemInform Abstract: Palladium‐Catalyzed Annulation of 2, 2′‐Diiodobiphenyls with Alkynes: Synthesis and Applications of Phenanthrenes. Issue 16 (28th March 2013) - Lin, Yu‐De; Cho, Chun‐Lung; Ko, Chih‐Wei; Pulte, Anna; Wu, Yao‐Ting
Abstract The present new method is also applicable to chiral alkynes like (XI) giving optically active products which can be smoothly converted into phenanthroindolizidine and phenanthroquinolizidine alkaloids by Pictet—Spengler reaction as shown for (XIV).